Find all School-related info fast with the new School-Specific MBA Forum

 It is currently 28 Jun 2016, 14:11

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# if xy>0, does (x-1)(y-1) = 1

 post reply Question banks Downloads My Bookmarks Reviews Important topics
Author Message
Intern
Joined: 26 Nov 2004
Posts: 47
Followers: 1

Kudos [?]: 0 [0], given: 0

if xy>0, does (x-1)(y-1) = 1 [#permalink]

### Show Tags

28 Nov 2004, 14:11
00:00

Difficulty:

(N/A)

Question Stats:

0% (00:00) correct 0% (00:00) wrong based on 0 sessions

### HideShow timer Statistics

This topic is locked. If you want to discuss this question please re-post it in the respective forum.

Just wondering if the answer in the OG is correct for the following problem.

if xy>0, does (x-1)(y-1) = 1

1) x+y = xy
2) x = y

what do you guys think.
Director
Joined: 31 Aug 2004
Posts: 610
Followers: 3

Kudos [?]: 96 [0], given: 0

### Show Tags

28 Nov 2004, 14:26
I pick A.

(1-x)(1-y)=1+xy-x-y=1+0=1

Numbers picking excludes statement 2
Intern
Joined: 26 Nov 2004
Posts: 47
Followers: 1

Kudos [?]: 0 [0], given: 0

### Show Tags

28 Nov 2004, 14:49
twixt wrote:
I pick A.

(1-x)(1-y)=1+xy-x-y=1+0=1

Numbers picking excludes statement 2

Correct twixt, i my thinking was a little bit messed up, i was thinking something like a D for answer. It just struck my mind that it should be A.
Intern
Joined: 14 Dec 2004
Posts: 1
Followers: 0

Kudos [?]: 0 [0], given: 0

### Show Tags

21 Dec 2004, 15:19
I pick b.
(x-1)(y-1) = 1
xy-x-y+1 = 1
xy-(x+y)= 1-1=0

Lets apply (1) means xy-xy = 0 but xy> 0.
lets apply (2) x= y means x^2-2x= 0.so x^2 = 2x x= 2=y.
xy>0 4>0.

please correct me if iam wrong
Manager
Joined: 13 Dec 2004
Posts: 51
Followers: 0

Kudos [?]: 4 [0], given: 0

### Show Tags

21 Dec 2004, 21:38
No, you're wrong. It's definitely not B. Just because xy>0 doesn't mean that xy-(x+y) isn't 0. I'm pretty sure the answer is A.
Director
Joined: 19 Nov 2004
Posts: 559
Location: SF Bay Area, USA
Followers: 4

Kudos [?]: 138 [0], given: 0

### Show Tags

22 Dec 2004, 14:50
Stem (x-1)(y-1) = 1 can be expanded to
xy -x-y+1=1
or
xy = x+y

A) says exactly this

B) B says x=y, the stem will be valid only if (y-1)^2=1, but we don't know that. So this is not it

A for this.
[#permalink] 22 Dec 2004, 14:50
Display posts from previous: Sort by

# if xy>0, does (x-1)(y-1) = 1

 post reply Question banks Downloads My Bookmarks Reviews Important topics

 Powered by phpBB © phpBB Group and phpBB SEO Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.